Discordant CAR-T cell signaling: implications of divergence from physiological T cell activation - Pablo Gonzalez-Garcia; Noelia Moares; Isabel Serrano-García; Ricardo Fernandez-Cisnal; Rosa Luna-Espejo; Javier Ocaña-Cuesta; Wenjie Yi-He; Juan P. Muñoz-Miranda; Antonio Gabucio; Cecilia M. Fernandez-Ponce; Francisco Garcia-Cozar (Journal of Translational Medicine)
Abstract Chimeric antigen receptor (CAR) T cell therapy constituted a recent breakthrough in the treatment of poor prognosis cancers by harnessing therapeutic T cells with an engineered non-MHC restricted antigen recognition transgene. CAR constructs are expressed in addition to endogenous T cell receptor (TCR) and utilize their activation machinery by a process still not yet fully understood. Despite the great success and widespread presence of CAR-T cells in clinical trials, they still have some shortcomings that may stem in part from their failure to fully mimic physiological TCR-mediated T cell activation, causing dysfunctional states and impaired responses that limit their persistence and causes incomplete remission of tumors or severe side effects. Recent studies have shown that much of the differences among CAR-T cell activation and natural TCRs occur early in the antigen recognition process, upon formation of the immune synapse when the first signaling events occur. In this review, by comparing the mechanisms of lymphocyte activation by CARs vs. TCRs, we will discuss how these chimeric constructs induce a stimulation characterized by un-orchestrated, incomplete, or impaired signaling events that in turn could explain some of their shortcomings.